The Effect of Additional Carrageenan on The Quality of Green Bean (Vigna radiata) Milk Ice Cream in Terms Viscosity, Density, Total Dissolved Solids, and Color - Panjaitan, Niko Dolly Imanuel; Armaini, Armaini (Faculty of Animal Science Universitas Brawijaya, 2024)
The aim of this research was to determine the effect of adding carrageenan on quality milk ice cream based on viscosity, density, total dissolved solid, and color L*a*b*. The material used in this research were full cream milk, skim milk, whipping cream, sugar, TBM emulsifier green bean flour, and carrageenan. The research method used was an experimental method without repetition with four treatments. Variables were tested 4 times in sample analysis. Carrageenan added to the milk ice cream formulation consists of treatment: 0% (T0); 0.3% (T1); 0.6% (T2); 0.9% (T3). The result showed that carrageenan addition gave an increased the viscosity, density, and total dissolved solid, but didn’t increase the L*a*b* color of the ice cream. The average value of viscosity is 5.45-16.55, density1.182-1.188, total dissolved solid 35.50-37.000brix, color L* 79.13-79.98, color a* -3.15-(-3.47), and b* 14.47-15.99. Based on the results of this research, it can be concluded that the addition of carrageenan with different concentration levels resulted in the viscosity value of milk ice cream increasing by 15.55cP and the L*a*b* color value not increasing, as well as increasing the density by 1.188% and total dissolved solid by 37.000Brix.